2013
DOI: 10.1002/oa.2319
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Healthy and Osteoarthritic Joint Surfaces in Archaeological Skeletons

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…As other studies (Plomp, Roberts, & Strand Viðarsdόttir, ; Weiss, ) have also reported a correlation between OA and chronological age, we might expect degenerative qualities to progress linearly, with the oldest persons with advanced OA expression being aged accurately using any one of the os coxa methods applied at a single joint surface. But joint changes of OA are a function of both the natural aging process and of the mechanical stress response to loading.…”
Section: Discussionmentioning
confidence: 77%
“…As other studies (Plomp, Roberts, & Strand Viðarsdόttir, ; Weiss, ) have also reported a correlation between OA and chronological age, we might expect degenerative qualities to progress linearly, with the oldest persons with advanced OA expression being aged accurately using any one of the os coxa methods applied at a single joint surface. But joint changes of OA are a function of both the natural aging process and of the mechanical stress response to loading.…”
Section: Discussionmentioning
confidence: 77%
“…Because the above risk factors for degenerative joint diseases enable us to reconstruct prehistoric life activities, many bioarchaeologists have investigated the degenerative changes of joints from ancient human populations (Jurmain, 1980, Merbs, 1983, Fukushima, 1988, Bridges, 1991, Lovell, 1994, Lieverse et al, 2007, Schrader, 2012, Woo and Sciulli, 2013, Plomp et al, 2013, Palmer et al, 2014. As the aforementioned studies show, many systematic factors, especially age, can affect the incidence of degenerative joint changes.…”
Section: Introductionmentioning
confidence: 99%
“…This analytical limitation has led to the development of aging methodologies examining degenerative changes within the skeleton . Degenerative changes are associated with chronological age and tend to be progressive .…”
mentioning
confidence: 99%
“…The osteoarthritic changes associated with age processes, namely natural cartilage degradation at the cellular level , increase the likelihood of developing the macroscopic, reactive changes commonly associated with the presence of OA. These include the proliferation of osteophyte growth along the joint margin and surface, the appearance of porosity on the joint surface, changes in bone contour, with the bone becoming wider and flatter in appearance, and the creation of eburnation, which presents as a highly polished, sometimes grooved area on the bone surface resulting from prolonged bone‐on‐bone contact . The additional risk factors for OA, which include biomechanical/occupational stress , trauma , genetics , and excessive bodyweight , play a fundamental role in the locational expression and severity of the macroscopic disease markers within skeletal joints .…”
mentioning
confidence: 99%